Interpreting the Chinese version of quality of life questionnaire for functional digestive disorders. Issue 4 (21st January 2018) - Hou, Zheng‐kun; Mi, Hong; Liu, Feng‐bin; Chen, Zhuo‐qun; Chen, Xin‐lin; Wu, Yu‐hang; Che, Xiao‐lu
Abstract: Background and Aim: The Chinese version quality of life questionnaire for functional digestive disorders (Chin‐FDDQL) is a useful health assessment instrument for functional dyspepsia. This study aims to identify its score interpretation for clinical practice. Methods: Data of Chin‐FDDQL from the functional dyspepsia patients (≥ 18 years) between November 2009 and April 2013 were enrolled in the 1st and 14th day. After baseline and responsiveness analysis, the single score interpretation and percentile ranks were established. The statistically reliable change was defined with effect size, standardized response mean, minimal detectable change, and others. Then the receiver operating characteristic curve analysis for health improvement was performed to define the clinically important change. Results: Two hundred two functional dyspepsia patients, 150 healthy participants, and 25 missing data were enrolled for analysis. Compared with the intake patients, the discharged and healthy persons have significant better health status in all domains ( P  < 0.001, expect discomfort in discharged people, P  = 0.142), totally contrast to missing data. The reliability for single total intake and discharge were both ± 1. Based on score distribution, the 25th, 50th, and 75th percentile ranks were 49, 58, and 66 for intake scores and 59, 65, and 72 for discharge scores, respectively. The minimal detectable change and Reliable Change Index were 6 and 11 for total score. Receiver operating characteristic analyses supported that total score changes 4 or more represented minimal clinically important improvement. Conclusions: The score interpretation system of the Chin‐FDDQL could assist clinician's decision making during the therapy practice.